2009
DOI: 10.1111/j.1365-2648.2008.04946.x
|View full text |Cite
|
Sign up to set email alerts
|

The emotional experiences of family carers in Huntington disease

Abstract: Aim This paper is a report of a study conducted to examine the emotional experience of caregiving by family carers of people with Huntington disease and to describe strategies they used to deal with that experience. Background Huntington disease, commonly diagnosed in young to middle adulthood, is an inherited single gene disorder involving loss of cognitive, motor and neuropsychiatric function. Many family members become caregivers as well as continuing as parents and wage earners. The emotional aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(103 citation statements)
references
References 24 publications
6
96
0
1
Order By: Relevance
“…Using the data obtained from the Behavioral Inventory, it was observed that the SG when compared to the CG showed statistically significant differences in internalizing factors (Table 1, Figure 2) and total problems (Table 1; Figure 4), suggesting that the behavioral profile with changes involves not only the individual but also the environment where he is inserted, consequently showing losses in his social relation [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the data obtained from the Behavioral Inventory, it was observed that the SG when compared to the CG showed statistically significant differences in internalizing factors (Table 1, Figure 2) and total problems (Table 1; Figure 4), suggesting that the behavioral profile with changes involves not only the individual but also the environment where he is inserted, consequently showing losses in his social relation [11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the DH impairs the mental health of individuals and may be observed suffering and emotional stress among family throughout the course of the disease 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with HD are cared for by informal carers, usually family members, who may themselves be at risk of inheriting the disease and/or have children who are at-risk of HD. The burden of providing emotional and practical support can be costly in terms of the carer's own mental and physical health (Williams et al, 2009). With the onset of HD occurring in mid-adulthood, there may be particular challenges that HD carers face through being at a life-stage where they are managing a career and looking after children (Aubeeluck and Moskowitz, 2008;Rolland and Williams, 2005;Williams et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The burden of providing emotional and practical support can be costly in terms of the carer's own mental and physical health (Williams et al, 2009). With the onset of HD occurring in mid-adulthood, there may be particular challenges that HD carers face through being at a life-stage where they are managing a career and looking after children (Aubeeluck and Moskowitz, 2008;Rolland and Williams, 2005;Williams et al, 2009). This can result in serious financial implications for HD families where the carer may have to end their job mid-career, potentially creating further stress.…”
Section: Introductionmentioning
confidence: 99%
“…Being a next of kin was described as experiencing disintegration of one's life. Spouses were distressed by the loss of the relationship with their spouse as an intimate partner [13]. Next of kin to young adults with multiple sclerosis experienced caregiver burden, i.e., physical, psychological, emotional, social, and economic stressors.…”
Section: Introductionmentioning
confidence: 99%